2002
DOI: 10.1097/00043426-200211000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Indwelling Central Venous Catheter-Related Complications in Children With Broviac or Clampless Valved Catheters

Abstract: There were no major differences in the incidence of mechanical or infectious complications between the two devices. Malfunction was more frequent in Broviac catheters, whereas catheter displacement occurred more frequently in clampless valved catheters. These results show the importance of central venous catheter-related mechanical complications in the management of children with hematologic or oncologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…Despite the unbalanced distribution of CVC type, our findings are consistent with previous reports. The increase in infectious 13 (5) 19 (2) 0 (0) 11 (4) 8 (1) 7 (3) 12 (2) OR (95%CI) (7) 105 (29) 85 (13) 58 (21) 133 (16) 10 (13) 46 (16) 87 (16) 42 (17) 101 (15) OR (95%CI) (3) 17 (5) 24 (4) 7 (3) 26 (3) 5 (7) 11 (4) 15 (3) 14 (6) 17 (3) OR (95%CI) risk when using externalized CVCs is probably offset by their atraumatic access, thereby justifying the continued use of this CVC type in all Italian pediatric cancer centers. In our study, the underlying disease was not a significant determinant of risk, in contrast with other studies which reported a higher risk of infection in children with acute leukemia [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unbalanced distribution of CVC type, our findings are consistent with previous reports. The increase in infectious 13 (5) 19 (2) 0 (0) 11 (4) 8 (1) 7 (3) 12 (2) OR (95%CI) (7) 105 (29) 85 (13) 58 (21) 133 (16) 10 (13) 46 (16) 87 (16) 42 (17) 101 (15) OR (95%CI) (3) 17 (5) 24 (4) 7 (3) 26 (3) 5 (7) 11 (4) 15 (3) 14 (6) 17 (3) OR (95%CI) risk when using externalized CVCs is probably offset by their atraumatic access, thereby justifying the continued use of this CVC type in all Italian pediatric cancer centers. In our study, the underlying disease was not a significant determinant of risk, in contrast with other studies which reported a higher risk of infection in children with acute leukemia [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have reported major complications associated with central lines, including thrombotic occlusion, infection, and mechanical malfunction 5–8. It has been suggested that the most common complication is infection, with thrombosis being a major complication as well 6,7.…”
Section: Discussionmentioning
confidence: 99%
“…A common morbidity associated with indwelling CVCs is catheter-related infection (CRI) with the incidence of infection ranging from 3% to 60% over the life span of the catheter [1,2]. Current Infectious Disease Society of America (IDSA) guidelines state that infected tunneled CVCs may be salvaged if the infection is uncomplicated and caused by coagulase-negative Staphylococcus spp, S aureus, or Gramnegative bacilli [1].…”
mentioning
confidence: 99%